Convenient syntheses of orthogonally protected aminocyclopentitols from aldopentoses. Issue 3 (14th January 2015) - Košak, Urban; Hrast, Martina; Knez, Damijan; Maraš, Nenad; Črnugelj, Martin; Gobec, Stanislav
Graphical abstract